Surface microscopy with low energy electrons - Bauer, Ernst (Springer New York, 2014)
This book, written by a pioneer in surface physics and thin film research and the inventor of Low Energy Electron Microscopy (LEEM), Spin-Polarized Low Energy Electron Microscopy (SPLEEM) and Spectroscopic Photo Emission and Low Energy Electron Microscopy (SPELEEM), covers these and other techniques for the imaging of surfaces with low energy (slow) electrons. These techniques also include Photoemission Electron Microscopy (PEEM), X-ray Photoemission Electron Microscopy (XPEEM), and their combination with microdiffraction and microspectroscopy, all of which use cathode lenses and slow electrons. Of particular interest are the fundamentals and applications of LEEM, PEEM, and XPEEM because of their widespread use. Numerous illustrations illuminate the fundamental aspects of the electron optics, the experimental setup, and particularly the application results with these instruments. Surface Microscopy with Low Energy Electrons will give the reader a unified picture of the imaging, diffraction, and spectroscopy methods that are possible using low energy electron microscopes. Provides a unified description of full-field, low energy electron microscopies Presents the basic theory and experiment of low energy emission and reflection Compares the possibilities and limitations of the various imaging methods Describes multi-method studies Contains an extensive list of references for easy access to the original literature